Feasibility of using a dose-area product ratio as beam quality specifier for photon beams with small field sizes. (January 2018) - Pimpinella, Maria; Caporali, Claudio; Guerra, Antonio Stefano; Silvi, Luca; De Coste, Vanessa; Petrucci, Assunta; Delaunay, Frank; Dufreneix, Stéphane; Gouriou, Jean; Ostrowsky, Aimé; Rapp, Benjamin; Bordy, Jean-Marc; et al.
Highlights: DAPR20, 10 properties are investigated in photon beams with field sizes below 2 cm. Influence of field size on photon spectrum and dosimetric parameters is evaluated. Measurements by ionization chambers with different characteristics are compared. Results on DAPR20, 10 obtained with two different accelerators are reported. Criteria to obtain a DAPR20, 10 useful as small beam quality index are discussed. Abstract: Purpose: To investigate the feasibility of using the ratio of dose-area product at 20 cm and 10 cm water depths ( DAPR 20, 10 ) as a beam quality specifier for radiotherapy photon beams with field diameter below 2 cm. Methods: Dose-area product was determined as the integral of absorbed dose to water ( D w ) over a surface larger than the beam size. 6 MV and 10 MV photon beams with field diameters from 0.75 cm to 2 cm were considered. Monte Carlo (MC) simulations were performed to calculate energy-dependent dosimetric parameters and to study the DAPR 20, 10 properties. Aspects relevant to DAPR 20, 10 measurement were explored using large-area plane-parallel ionization chambers with different diameters. Results: DAPR 20, 10 was nearly independent of field size in line with the small differences among the corresponding mean beam energies. Both MC and experimental results showed a dependence of DAPR 20, 10 on the measurement setup and the surface over which D w is integrated. For a given setup, DAPR 20, 10 values obtained using ionization chambers with different air-cavity diameters agreed with one another within 0.4%, after the application of MC correction factors accounting for effects due to the chamber size. DAPR 20, 10 differences among the small field sizes were within 1% and sensitivity to the beam energy resulted similar to that of established beam quality specifiers based on the point measurement of D w . Conclusions: For a specific measurement setup and integration area, DAPR 20, 10 proved suitable to specify the beam quality of small photon beams for the selection of energy-dependent dosimetric parameters.